Involvement of organic systems in golden retriever X-linked muscular dystrophy - Miyazato, Ligia G. [UNESP]; Beretta, Daniel C. [UNESP]; Engracia-Filho, Jair R.; Moraes, Flavio R. [UNESP]; Moraes, Julieta R.E. [UNESP] (My University, 2011)
Duchenne muscular dystrophy is a lethal genetic disease characterized by progressive muscle degeneration that usually had been used the Golden Retriever as a model for studying the disease (GRMD - Golden Retriever Muscular Dystrophy). A total of 16 male dystrophic Golden Retrievers dogs between 5 to 51 months of age were examined in the present study. The animals were classified as dystrophic according to two simultaneous complementary criteria: genotypic analysis and serum creatine kinase levels. The macroscopic abnormalities of the different organs and tissues and histopathological features were described using hematoxylin-eosin. The lesions in the skeletal muscles associated with the digestive problems resulted in cachexia with different intensities in all the dystrophic dogs. Cardiac muscle involvement was found in 87,5% of the GRMD dogs resulting, however, in cardiac failure in only 18,8% of the animals. The musculature of the diaphragm was hypertrophic in all affected animals resulting in progressive respiratory muscle weakness and at later stages in respiratory failure (81,25%). The liver abnormalities found in dystrophic dogs were originated mainly from heart disease and developed progressively. Hyperemia of mucosa and granular material indicated changes in the functioning and emptying of bladder. The germinative lineage cells presented moderate to severe degeneration probably due to degeneration of the scrotum and cremaster muscle which prevented the proper thermo-regulation of the testicle. Our results highlight the fact that there is significant impairment of the cardiac, respiratory and skeletal muscle systems in GRMD dogs since the age of five months. In addition, significant alterations of the gastrointestinal tract, urinary and reproductive systems are indicating the presence of degenerative lesions in the smooth musculature.
Keywords: Golden retriever; Gross morphology; Histological features; Muscular dystrophy; Animalia; Canis familiaris